ORAL TRADITION OF MITONI JAVA CULTURE IN PADANG VILLAGEBINTUNGAN DHARMASRAYA DISTRICT (SEMIOTIC STUDY): TRADISI LISAN BUDAYA JAWA MITONI DI DUSUN PADANG BINTUNGAN KABUPATEN DHARMASRAYA (KAJIAN SEMIOTIKA) - Regita Agustina; Yulia Sri Hartati; Zulfitriyani Zulfitriyani (Jurnal Kata, 2023)
Language errors are deviations from the language level which are influenced by various factors. The purpose of this research is to identify and describe the types and factors that cause language errors in student narrative texts and how to overcome language errors in student essays. This research is a qualitative descriptive study using the Miles-Hubermen technique with the stages of data reduction, data presentation, and drawing conclusions. The object of this study are 11 narrative texts written by grade IV students with research subjects in the form of words, sentences, and spellings that contained language errors. Based on the research conducted, it is found that language errors in grade IV students that commonly occur, namely errors in diction selection, spelling in the form of capital letters and punctuation, as well as sentence irregularities are caused by internal and external factors of students.